PENGELOLAAN RUANG KELAS DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS III DI SDN 1 UJUNG TANJUNG - Selve Yeder; Yulaini, Erma; Utomo, Budi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze classroom management in increasing students' learning interest at SDN 1 Ujung Tanjung. Using a qualitative descriptive method, data were collected through student questionnaires, teacher interviews, and classroom documentation. The results indicate that the four main aspects of classroom management—visibility, accessibility, flexibility, and comfort—play an essential role in creating a conducive learning environment. These elements positively affect students’motivation and engagement during the learning process. The findings also show that students' learning interest improves in classrooms that are well-organized, visually stimulating, and supportive of interaction. It is concluded that classroom management is not merely a technical issue but a strategic component in enhancing primary school students' learning outcomes.